Posouzení stavebně-technického stavu stokové sítě - Hladíková, Michaela (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Bakalářská práce se zabývá problematikou průzkumu a hodnocení technického stavu stokových sítí, s důrazem na poruchy tuhého potrubí a možnosti jeho sanace. Práce je rozdělena na dvě části. V teoretické části je zpracována rešerše sanačních metod vhodných pro opravy tuhých kanalizačních potrubí,včetně oblastí použití a technologických postupů aplikace. Dále jsou popsány typologie poruch a přehled hodnoticích metod technického stavu sítí podle platných českých i evropských norem. V praktické části bylo provedeno hodnocení vybraného úseku kanalizační sítě na základě kamerové prohlídky, zatřídění poruch podle kódovacího systému ČSN EN 13508-2+A1 a bodového hodnocení dle TNV 75 6905. Práce se zaměřuje na posouzení vhodnosti těchto metod při návrhu technických řešení a jejich využitelnosti v rámci správy a obnovy kanalizační infrastruktury.

The bachelor thesis deals with the issue of research and evaluation of the technical condition of sewer networks, with emphasis on the failures of rigid pipes and the possibilities of their rehabilitation. The thesis is divided into two parts. In the theoretical part, a survey of rehabilitation methods suitable for the repair of rigid sewer pipes is prepared, including the areas of application and technological procedures of application. Furthermore, the typologies of failures and an overview of the assessment methods of the technical condition of networks according to the valid Czech and European standards are described. In the practical part, the evaluation of a selected section of the sewer network was carried out on the basis of a camera inspection, classification of failures according to the coding system of ČSN EN 13508-2+A1 and scoring according to TNV 75 6905. The work focuses on the assessment of the suitability of these methods in the design of technical solutions and their applicability in the management and rehabilitation of sewerage infrastructure.
Assessment of the Construction and Technical Condition of the Sewer Network
Keywords: Stoková síť; technický stav; inspekce; poruchy; vyhodnocení; Sewer network; technical condition; inspection; failures; evaluation